Baseline Triglyceride Level Affected the Efficacy of Vildagliptin in Treating Type 2 Diabetes: A Post Hoc Analysis of the VISION Study. (8th August 2019) - Zhou, Lingli; Cai, Xiaoling; Luo, Yingying; Zhang, Fang; Ji, Linong
Abstract : Identifying factors that may impact vildagliptin's efficacy could contribute to individualized treatment for patients with type 2 diabetes. In the current study, we aimed to assess the correlation between patient baseline triglyceride (TG) and efficacy of vildagliptin in Chinese patients with type 2 diabetes in a post hoc analysis of the VISION study. TG-based subgroup analysis was performed to evaluate baseline TG's impact on the decrease of glycated hemoglobin (HbA1c ) in patients receiving vildagliptin plus low-dose metformin (VLDM) vs. high-dose metformin (HDM). Additionally, multivariate linear regression was performed to assess the association between baseline TG and HbA1c reduction at weeks 12 and 24 for patients receiving VLDM vs. HDM. For patients receiving VLDM, baselineTG ≤ 2.03 mmol/L was associated with significantly greater HbA1c reduction vs.TG > 2.03 mmol/L at week 12, but not at week 24. Additionally, multivariate linear regression analysis revealed a significant independent association and an association short of statistical significance between patient baseline TG and the HbA1c -reducing efficacy of VLDM at weeks 12 (P < 0.001 ) and 24 (P = 0.082 ), respectively, while such association was absent for HDM. Collectively, baseline TG was an independent predictive factor for the efficacy of a dipeptidyl peptidase-IV in treating type 2 diabetes during its initial use.